2009
DOI: 10.2147/vhrm.s7464
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and coronary vascular endothelium adaptations in hypertension

Abstract: This review highlights a number of nitric oxide (NO)-related mechanisms that contribute to coronary vascular function and that are likely affected by hypertension and thus become important clinically as potential considerations in prevention, diagnosis, and treatment of coronary complications of hypertension. Coronary vascular resistance is elevated in hypertension in part due to impaired endothelium-dependent function of coronary arteries. Several lines of evidence suggest that other NO synthase isoforms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 137 publications
1
7
0
Order By: Relevance
“…Previous studies also supported the lower NO bioavailability in hypertensive subjects [ 15 17 ]. Higher production of reactive oxygen species, lower endothelial NO synthase expression, and/or impaired L-arginine uptake are possible mechanisms for reduced NO bioavailability in hypertensive subjects [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Previous studies also supported the lower NO bioavailability in hypertensive subjects [ 15 17 ]. Higher production of reactive oxygen species, lower endothelial NO synthase expression, and/or impaired L-arginine uptake are possible mechanisms for reduced NO bioavailability in hypertensive subjects [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 55%
“…[ 18 ] Reduced NO bioavailability in hypertensive subjects has been documented in previous studies,[ 10 23 24 ] and different mechanisms have been suggested for reduced availability of NO during hypertension, including the generation of reactive oxygen species, impaired l-arginine uptake,[ 23 ] or reduced NOS expression. [ 24 ]…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the pathologies studied, the presence of aneurisms contributes to endothelial dysfunction and the increase in the NO 3 − and NO 2 − ratio can favor the increase of peroxynitrites. In addition, altered NO bioavailability contributes to the modified vasomotion in hypertension [ 95 ] where an increased production of ROS is associated with an elevated production of peroxynitrite in coronary blood vessels. Endothelial dysfunction also promotes an increase in the generation of O 2 − leading to an enhanced NO inactivation against peroxynitrites [ 93 ].…”
Section: Discussionmentioning
confidence: 99%